The Effective General College Curriculum as Revealed by Examinations (Book collections on Project MUSE., 1937)
The Effective General College Curriculum as Revealed by Examinations was first published in 1937. Minnesota Archive Editions uses digital technology to make long-unavailable books once again accessible, and are published unaltered from the original University of Minnesota Press editions. This volume, authored by the Committee on Education Research of the University of Minnesota, is the ninth in a series dealing with obstacles and challenges in college education. The General College of the University of Minnesota was established in 1932 as an experiment in giving students who cannot spend four ye.